APLIKASI PASAL 56 AYAT (1) KUHAP SEBAGAI KEWAJIBAN HUKUM DALAM PENYELESAIAN PERKARA PIDANA PADA TINGKAT PENYIDIKAN (STUDI KASUS DI POLRESTA PONTIANAK) - MUHAMMAD MUSA SURIN, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2012)
AbstractThis thesis discusses the application of Article 56 paragraph (1) Criminal Procedure Code as a legal obligation in the settlement of criminal cases at the level of investigation at the Police Pontianak. In addition, it also has the objective is to reveal and analyze the application of Article 56 Paragraph (1) Criminal Procedure Code as a legal obligation in the settlement of criminal cases at the level of investigation at the Police Pontianak, the factors that hinder the application of Article 56 Paragraph (1) Criminal Procedure Code as a legal obligation in settlement of criminal cases at the level of investigation in the United Kingdom Police and legal efforts are being made to apply Article 56 Paragraph (1) Criminal Procedure Code as a legal obligation in the settlement of criminal cases at the level of investigation at the Police Pontianak.Key words : Application of Article 56 Paragraph (1) of the Criminal CodeAbstrakTesis ini membahas tentang aplikasi Pasal 56 ayat (1) KUHAP sebagai kewajiban hukum dalam penyelesaian perkara pidana pada tingkat penyidikan di Polresta Pontianak. Di samping itu juga mempunyai tujuan yaitu untuk mengungkapkan dan menganalisis aplikasi Pasal 56 Ayat (1) KUHAP sebagai kewajiban hukum dalam penyelesaian perkara pidana pada tingkat penyidikan di Polresta Pontianak, faktor-faktor yang menghambat aplikasi Pasal 56 Ayat (1) KUHAP sebagai kewajiban hukum dalam penyelesaian perkara pidana pada tingkat penyidikan di Polresta Pontianak serta upaya hukum yang dilakukan untuk mengaplikasikan Pasal 56 Ayat (1) KUHAP sebagai kewajiban hukum dalam penyelesaian perkara pidana pada tingkat penyidikan di Polresta Pontianak.Kata Kunci : Aplikasi Pasal 56 Ayat (1) KUHP,